A high-strength stress absorbing patch

By designing a high-strength stress-absorbing sticker for asphalt road construction, the problem of reflective cracks and rutting in asphalt concrete overlays is solved, and the anti-skid, noise reduction, durability and driving comfort of the road are improved. Production costs and workload are reduced at the same time.

CN111139706BActive Publication Date: 2025-01-21NANJING SUER ENG MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202010040274.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-01-15
Publication Date
2025-01-21
Estimated Expiration
2040-01-15

AI Technical Summary

Technical Problem

The lack of high-performance stress absorption patches in existing asphalt road construction results in the asphalt concrete paving prone to reflective cracks and ruts, which increases production costs and workloads.

Method used

Design a high-strength stress-absorbing patch, including the main body of the absorbing patch and an isolation layer. The main body of the absorbing patch is composed of high-strength quartz sand, modified polymer, asphalt and other materials, and has the functions of stress absorption, interlayer bonding and waterproofing.

Benefits of technology

By laying high-strength stress-absorbing stickers, reflective cracks and ruts can be comprehensively prevented, the road's anti-skid, noise reduction, durability and driving comfort can be improved, while production costs and workloads can be reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN111139706B_ABST
    Figure CN111139706B_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength stress absorbing patch, including an absorbing patch main body, an isolation layer evenly applied on the absorbing patch main body, and the isolation layer main body is a high-strength and clean quartz sand of 20-60 mesh; the tire base of the absorbing patch main body is soaked by a modified polymer, and no unsoaked stripes appear. The advantages of the present invention compared with the prior art are: it has stress absorption, interlayer bonding and waterproofing functions, as an integrated road interlayer transition material, a high-performance tire base cloth with good flexural resistance, high tensile strength and corrosion resistance is selected as the base material, and is compounded at high temperature in a high-performance viscoelastic material with high softening point and good low-temperature flexibility. As a new type of composite geosynthetics with waterproof, anti-cracking, large deformation and transition bonding layer functions developed after integrating "anti-cracking patch, road and bridge waterproofing membrane, AR-SAMI", it has good compatibility with asphalt mixture, and is only accompanied by slight deformation under high temperature and rolling conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road construction, in particular to a high-strength stress absorbing patch. Background Art

[0002] Cement concrete pavement, also known as white pavement, was once a common pavement structure for urban roads because of its high strength, long life, simple construction and low cost. However, with the development of cities, the traffic volume has increased dramatically, and the shortcomings of cement concrete pavement, such as high noise, bumpy plate joints, poor driving comfort and long maintenance period, have become increasingly prominent. Therefore, in recent years, various cities have adopted the method of adding asphalt concrete surface layer to transform it (commonly known as white plus black pavement), which can not only avoid the waste of resources caused by excavating the old pavement, but also greatly improve the anti-skid, noise reduction, durability and driving comfort of the road pavement surface layer. At present, in the white plus black transformation, most of the asphalt concrete surface layer is directly paved on the old cement concrete pavement. The process is simple, and the following two problems gradually emerge during use: First, the cracks and plate joints of the old cement concrete pavement are not specially treated, resulting in the occurrence of reflective cracks in the asphalt concrete overlay layer; second, cement concrete is a rigid base layer and does not have good load, stress and deformation diffusion capabilities, resulting in the occurrence of rutting in the asphalt concrete overlay layer.

[0003] In order to prevent structural reflective cracks in asphalt road projects and thermal shrinkage cracks and load-type shear cracks between cement slabs in white-on-black road reconstruction projects from being reflected to the surface layer, a layer of high-performance stress absorption sticker is laid between cement slabs, water-stabilizing agent or asphalt structural layers to comprehensively prevent reflective cracks, foundation water damage and other diseases, while also serving as an overall sealing waterproof layer and adhesive layer.

[0004] Therefore, it is imperative to design a high-strength stress absorbing patch. Summary of the invention

[0005] The technical problem to be solved by the present invention is the lack of a high-performance stress-absorbing patch in existing asphalt road construction applications, which makes the asphalt concrete overlay layer prone to reflective cracks and lacks good load, stress and deformation diffusion capabilities, resulting in rutting in the asphalt concrete overlay layer, which not only increases production costs but also increases the workload of personnel.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is as follows: a high-strength stress absorbing patch, comprising an absorbing patch main body, an isolation layer is evenly applied on the absorbing patch main body, and the isolation layer main body is high-strength and clean quartz sand of 20-60 mesh;

[0007] The specific specifications of the absorbent patch are as follows:

[0008] (1) The overall unit mass is 3.0±10%Kg / ㎡;

[0009] (2) Overall thickness is 2.5±5% mm;

[0010] (3) Longitudinal breaking strength ≥ 7KN / 200mm; transverse breaking strength ≥ 9KN / 200mm;

[0011] (4) Longitudinal and transverse elongation of 3-10%;

[0012] (5) Longitudinal trapezoidal tearing strength ≥ 300N; transverse trapezoidal tearing strength ≥ 400N;

[0013] (6) CBR bursting strength ≥ 2.5KN;

[0014] (7) Waterproof: tested at 0.3Mpa for 120 minutes to achieve watertightness;

[0015] (8) Heat resistance: no flowing or dripping when tested at 70°C;

[0016] (9) Low temperature flexibility, no cracks at -15°C;

[0017] The base of the absorbent patch body is soaked with the modified polymer, and no unsoaked stripes appear.

[0018] The advantages of the present invention compared with the prior art are: it has stress absorption, interlayer bonding and waterproofing functions. As an integrated road interlayer transition material, the present invention selects a high-performance tire base cloth with good flexural resistance, high tensile strength and corrosion resistance as the base material, and is compounded at high temperature in a high-performance viscoelastic material with a high softening point and good low-temperature flexibility. As a new type of composite geosynthetics with waterproofing, crack prevention, large deformation and transition bonding layer functions developed after integrating "anti-cracking stickers, road and bridge waterproofing membranes, AR-SAMI", the present invention has good compatibility with asphalt mixtures and is only accompanied by slight deformation under high temperature and rolling conditions.

[0019] As an improvement, the preparation process of the absorbent patch body includes a material batching system and a production line system;

[0020] The material batching system consists of a grinder and a mixing tank, and its preparation process is as follows:

[0021] During production, first deliver asphalt to the metering mixing tank according to the formula quantity, then add SBS according to the formula quantity, stir and melt, add other modifiers, and after melting, grind the mixture through an asphalt colloid mill. Grind and stir for no less than 30 minutes, and then add fillers to mix and stir.

[0022] The production line system transports the modified mixture generated by the material batching system to the oil coating pool, and then immerses the base into the pool. The oiled felt body is coated with sand, that is, an isolation layer is set on the main body of the absorbent patch according to the standard, and then calendered and cooled to form a finished product.

[0023] As an improvement, the following specific steps are provided in the material batching system preparation process:

[0024] (1) Measuring: asphalt, SBS modifier, styrene-butadiene rubber powder, modified material and filler are electronically measured according to the formula quantity and batching sequence and then input into the batching tank;

[0025] (2) Batching and grinding: Add asphalt and base oil according to the formula quantity into the batching tank, start stirring, and control the temperature in the tank to 180℃±5℃;

[0026] Add SBS into the batching tank according to the formula quantity, control the temperature at 175℃-195℃ and stir to melt for 1h;

[0027] Input the modifier into the batching tank according to the formula quantity, control the temperature at 200℃-215℃ and stir to melt for 4-5 hours, and grind after melting, the grinding temperature is 190~220℃, and the grinding time is not less than 30min.

[0028] After grinding, add fillers according to the recipe quantity and stir for 30 minutes;

[0029] As an improvement, the preparation process of the production line system includes the following specific steps:

[0030] (1) Prepreg and coating: the prepreg oiling temperature is controlled between 190 and 210°C to completely soak the carcass; the coating oiling temperature is controlled between 170 and 200°C; the coating material should be no less than 3 / 4 of the depth of the oiling pool;

[0031] It is squeezed to the specified thickness by the upper and lower rollers of the pressing roller, and then cooled and coated by the cooling water roller and the tire film coating machine before being transported to the cutting and winding unit;

[0032] (2) After the prepared dipping material has passed the inspection, the oil temperature is maintained at 170-200°C for standby use, and production is stopped when the temperature is lower than 170°C;

[0033] Product quality is inspected according to the LHYN-anti-crack sticker Q31 standard requirements;

[0034] (3) Roll packaging: Products of different models and lengths shall be packaged and placed separately in accordance with regulations and affixed with qualified labels;

[0035] As an improvement, the preparation process of the absorbent patch body has process indicators:

[0036] (1) Hot oil furnace inlet and outlet temperature: 220~290℃;

[0037] (2) Finished material temperature: Finished material temperature 170~200℃;

[0038] (3) Coil oil coating temperature: 170-200°C; pre-oiling temperature: 190-210°C;

[0039] (4) Laminating temperature: 130-180℃;

[0040] (5) Cooling water temperature: ≤45℃;

[0041] (6) Oil softening point: 45-70°C;

[0042] (7) Oil softening point: 85~105℃.

[0043] As an improvement, the process indicators are sampled once for each production tank.

[0044] As an improvement, the raw materials in the preparation process of the absorbent patch body are as follows: asphalt 46-55%, SBS 7-10%, SIS1-3%, softening oil 8-15%, asphalt modifier 5-7%, additive 0.8-1.5% and filler 15-22%. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a structural schematic diagram of a high-strength stress-absorbing patch.

[0046] Figure 2 This is a schematic diagram of the preparation process of a high-strength stress absorption patch.

[0047] As shown in the figure: 1. Absorbent patch body, 2. Isolation layer. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below in conjunction with the accompanying drawings.

[0049] In the specific implementation of the present invention, a high-strength stress absorption patch includes an absorption patch body 2, on which an isolation layer 1 is evenly applied, and the isolation layer 1 is mainly made of high-strength and clean quartz sand with a mesh size of 20-60;

[0050] The specific specifications of the absorbent patch body 2 are as follows:

[0051] (1) The overall unit mass is 3.0±10%Kg / ㎡;

[0052] (2) Overall thickness is 2.5±5% mm;

[0053] (3) Longitudinal breaking strength ≥ 7KN / 200mm; transverse breaking strength ≥ 9KN / 200mm;

[0054] (4) Longitudinal and transverse elongation of 3-10%;

[0055] (5) Longitudinal trapezoidal tearing strength ≥ 300N; transverse trapezoidal tearing strength ≥ 400N;

[0056] (6) CBR bursting strength ≥ 2.5KN;

[0057] (7) Waterproof: tested at 0.3Mpa for 120 minutes to achieve watertightness;

[0058] (8) Heat resistance: no flowing or dripping when tested at 70°C;

[0059] (9) Low temperature flexibility, no cracks at -15°C;

[0060] The base of the absorbent patch main body 2 is soaked in the modified polymer, and no unsoaked stripes appear.

[0061] The preparation process of the absorbent patch body 2 includes a material batching system and a production line system;

[0062] The material batching system is composed of a grinder and a mixing tank, and its preparation process is as follows:

[0063] During production, first deliver asphalt to the metering mixing tank according to the formula quantity, then add SBS according to the formula quantity, stir and melt, add other modifiers, and after melting, grind the mixture through an asphalt colloid mill. Grind and stir for no less than 30 minutes, and then add fillers to mix and stir.

[0064] The production line system conveys the modified mixture generated by the material batching system to the oil coating pool, and then immerses the base into the pool. The oiled felt body is coated with sand, that is, the isolation layer 1 is set on the absorbent patch body 2 according to the standard, and the finished product is made after calendering and cooling.

[0065] The preparation process of the material batching system includes the following specific steps:

[0066] (1) Measuring: asphalt, SBS modifier, styrene-butadiene rubber powder, modified material and filler are electronically measured according to the formula quantity and batching sequence and then input into the batching tank;

[0067] (2) Batching and grinding: Add asphalt and base oil according to the formula quantity into the batching tank, start stirring, and control the temperature in the tank to 180℃±5℃;

[0068] Add SBS into the batching tank according to the formula quantity, control the temperature at 175℃-195℃ and stir to melt for 1h;

[0069] Input the modifier into the batching tank according to the formula quantity, control the temperature at 200℃-215℃ and stir to melt for 4-5 hours, and grind after melting, the grinding temperature is 190~220℃, and the grinding time is not less than 30min.

[0070] After grinding, add fillers according to the recipe quantity and stir for 30 minutes;

[0071] The preparation process of the production line system includes the following specific steps:

[0072] (1) Prepreg and coating: the prepreg oiling temperature is controlled between 190 and 210°C to completely soak the carcass; the coating oiling temperature is controlled between 170 and 200°C; the coating material should be no less than 3 / 4 of the depth of the oiling pool;

[0073] It is squeezed to the specified thickness by the upper and lower rollers of the pressing roller, and then cooled and coated by the cooling water roller and the tire film coating machine before being transported to the cutting and winding unit;

[0074] (2) After the prepared dipping material has passed the inspection, the oil temperature is maintained at 170-200°C for standby use, and production is stopped when the temperature is lower than 170°C;

[0075] Product quality is inspected according to the LHYN-anti-crack sticker Q31 standard requirements;

[0076] (3) Roll packaging: Products of different models and lengths shall be packaged and placed separately in accordance with regulations and affixed with qualified labels;

[0077] The preparation process of the absorbent patch body 2 has process indicators:

[0078] (1) Hot oil furnace inlet and outlet temperature: 220~290℃;

[0079] (2) Finished material temperature: Finished material temperature 170~200℃;

[0080] (3) Coil oil coating temperature: 170-200°C; pre-oiling temperature: 190-210°C;

[0081] (4) Laminating temperature: 130-180℃;

[0082] (5) Cooling water temperature: ≤45℃;

[0083] (6) Oil softening point: 45-70°C;

[0084] (7) Oil softening point: 85~105℃.

[0085] The above-mentioned process indicators are sampled and tested once for each production tank.

[0086] The raw materials in the preparation process of the absorbent patch body 2 are as follows: asphalt 46-55%, SBS 7-10%, SIS 1-3%, softening oil 8-15%, asphalt modifier 5-7%, auxiliary agent 0.8-1.5% and filler 15-22%.

[0087] The working principle of the present invention is as follows: in order to prevent structural reflective cracks in asphalt road projects and thermal shrinkage cracks and load-type shear cracks between cement slabs in white-on-black road reconstruction projects from being reflected to the surface layer, a layer of the present invention is laid between cement slabs, water-stabilizing agents or asphalt structural layers, which can comprehensively prevent reflective cracks, foundation water damage and other diseases, while also playing the role of an overall sealing waterproof layer and adhesive layer.

[0088] The anti-cracking performance of the invention meets the technical specification requirements of JT / T971-2015 polymer modified asphalt resistance tape for asphalt overlay, and the waterproof performance meets the standard specification requirements of JC / T974-2005 modified asphalt waterproof membrane for roads and bridges.

[0089] Specific use of the present invention:

[0090] (1) Clean and sweep the construction surface;

[0091] (2) Spraying adhesive layer oil

[0092] Before laying high-performance stress-absorbing stickers, the construction site should be evenly sprayed with emulsified asphalt tack oil with a solid content of ≥50%, with a dosage of 0.5-1L / m 2 (Depending on the roughness of the structural layer), after the emulsified asphalt is demulsified and the water evaporates completely, high-performance stress absorption tape is laid;

[0093] (3) Laying high-strength stress absorption stickers

[0094] Unroll the rolled high-performance stress-absorbing sticker according to the required width, with the isolation film facing down, tear off the isolation film underneath, and lay the high-performance stress-absorbing sticker flatly on the base surface.

[0095] If the design requires local joint patching, take the crack as the center line, unfold the rolled high-performance stress-absorbing sticker, take the expansion joint (crack) as the center line, and lay 1 / 2 on each side of the anti-crack area. With the isolation film facing down, tear off the isolation film underneath, and lay the high-performance stress-absorbing sticker flatly on the base surface;

[0096] (4) After the high-strength stress-absorbing tape is laid, use a rubber wheel machine or a pressure roller to flatten the high-strength stress-absorbing tape;

[0097] (5) When two high-strength stress-absorbing stickers overlap, the width should be 5 to 10 cm, and the overlap should be compacted with a roller to ensure a firm bond;

[0098] (6) Spread asphalt concrete directly on the paved high-strength stress-absorbing tape.

[0099] The invention has the characteristics of environmental protection and regeneration. The fibers in the absorbent patch can be broken when used, and the performance of the old asphalt mixture can be significantly improved after being recycled.

[0100] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features, and in the description of the present invention, "plurality" means two or more, unless otherwise clearly defined.

[0101] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0102] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is lower in level than the second feature.

[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A high-strength stress absorbing patch, comprising an absorbing patch body (2), characterized in that: An isolation layer (1) is evenly applied on the main body (2) of the absorbent patch, and the main body of the isolation layer (1) is high-strength and clean quartz sand of 20-60 mesh; The specific specifications of the absorbent patch body (2) are as follows: (1) The overall unit mass is 3.0±10%Kg / ㎡; (2) Overall thickness is 2.5±5% mm; (3) Longitudinal breaking strength ≥ 7KN / 200mm; transverse breaking strength ≥ 9KN / 200mm; (4) Longitudinal and transverse elongation of 3-10%; (5) Longitudinal trapezoidal tearing strength ≥ 300N; transverse trapezoidal tearing strength ≥ 400N; (6) CBR bursting strength ≥ 2.5KN; (7) Waterproof: tested at 0.3Mpa for 120 minutes to achieve watertightness; (8) Heat resistance: no flowing or dripping when tested at 70°C; (9) Low temperature flexibility, no cracks at -15°C; The base of the absorbent patch main body (2) is soaked with the modified polymer, and no unsoaked stripes appear. The raw materials in the preparation process of the absorbent patch main body (2) are asphalt 46-55%, SBS 7-10%, SIS1-3%, softening oil 8-15%, asphalt modifier 5-7%, auxiliary agent 0.8-1.5% and filler 15-22%; The preparation process of the absorbent patch body (2) includes a material batching system and a production line system. The material batching system is composed of a grinder and a mixing tank. During production, asphalt is first transported to a metering mixing tank according to the formula quantity, and then SBS is added according to the formula quantity. After stirring and melting, other modifiers are added. After melting, the mixture is ground through an asphalt colloid mill. The grinding and stirring are performed for not less than 30 minutes, and then fillers are added for mixing and stirring. The production line system transports the modified mixture generated by the material batching system to an oiling pool, and then immerses the base into the pool. The oiled felt body is coated with sand, that is, the isolation layer (1) is set on the absorbent patch body (2) according to the standard, and the finished product is made after calendering and cooling. The preparation process of the material batching system includes the following specific steps: (1) Measuring: asphalt, SBS modifier, styrene-butadiene rubber powder, modified material and filler are electronically measured according to the formula quantity and batching sequence and then input into the batching tank; (2) Batching and grinding: Add asphalt and base oil according to the formula quantity into the batching tank, start stirring, and control the temperature in the tank to 180℃±5℃; Add SBS into the batching tank according to the formula quantity, control the temperature at 175℃-195℃ and stir to melt for 1h; Put the modifier into the batching tank according to the formula quantity, control the temperature at 200℃-215℃ and stir to melt for 4-5 hours, and grind it after melting, the grinding temperature is 190~220℃, and the grinding time is not less than 30min; After grinding, add fillers according to the recipe quantity and stir for 30 minutes; The preparation process of the production line system includes the following specific steps: (1) Prepreg and coating: the prepreg oiling temperature is controlled at 190-210℃ to completely soak the carcass; the coating temperature is controlled between 170-200℃; the coating material should be no less than 3 / 4 of the depth of the oiling pool; It is squeezed to the specified thickness by the upper and lower rollers of the pressing roller, and then cooled and coated by the cooling water roller and the tire film coating machine before being transported to the cutting and winding unit; (2) After the prepared dipping material has passed the inspection, the oil temperature is maintained at 170-200°C for standby use, and production is stopped when the temperature is lower than 170°C; Product quality is inspected according to the LHYN-anti-crack sticker Q31 standard requirements; (3) For roll packaging, products of different models and lengths shall be packaged separately in accordance with regulations and affixed with qualified labels.

2. A high-strength stress absorbing patch according to claim 1, characterized in that: The preparation process of the absorbent patch body (2) has the following process indicators: (1) Hot oil furnace inlet and outlet temperature: 220~290℃; (2) Finished material temperature: Finished material temperature 170~200℃; (3) Coil oil coating temperature: 170-200°C; pre-oiling temperature: 190-210°C; (4) Laminating temperature: 130-180℃; (5) Cooling water temperature: ≤45℃; (6) Oil softening point: 45-70°C; (7) Oil softening point: 85~105℃.

3. A high-strength stress absorbing patch according to claim 2, characterized in that: The above-mentioned process indicators are sampled and tested once for each production tank.

Citation Information

Patent Citations

  • High-strength stress absorption patch

    CN212357865U